(untitled) (Zbornik Pravnog fakulteta Sveučilišta u Rijeci, 2022)
Measures taken to restrain the spread of the coronavirus have significantly impacted people’s well-being and behaviour, increasing thereby the likelihood of family violence, especially of violence against women. This paper tests the hypothesis that family violence has increased during the epidemic in Slovenia by analysing police datasets on reported cases of family violence in Slovenia during the pandemic. The results, which were confirmed by a series of t-tests, indicate that compared to a 10-year average, in 2020 there was an average number of reports of family violence, in contrast to a 20% lower number of reports in 2021. Similarly, the number of misdemeanours of family violence was almost average in 2020, and lower in 2021. Likewise, the number of restraining orders imposed in 2020 and 2021 was close to the above-mentioned 10-year average. Within a period of eleven weeks during both the first and the second lockdown period, there were higher instances of detected criminal offences and misdemeanours, whereas the number of restraining orders imposed and breached decreased.